Beta-Lactams Therapeutic Monitoring in Septic Children–What Target Are We Aiming for? A Scoping Review - Morales Junior, Ronaldo; Pereira, Gabriela Otofuji; Tiguman, Gustavo Magno Baldin; Juodinis, Vanessa D'Amaro; Telles, João Paulo; de Souza, Daniela Carla; Santos, Silvia Regina Cavani Jorge (Frontiers in Pediatrics, 2022)
The antimicrobial therapy of sepsis and septic shock should be individualized based on pharmacokinetic/pharmacodynamic (PK/PD) parameters to deliver effective and timely treatment of life-threatening infections. We conducted a literature scoping review to identify therapeutic targets of beta-lactam antibiotics in septic pediatric patients and the strategies that have been applied to overcome sepsis-related altered pharmacokinetics and increase target attainment against susceptible pathogens. A systematic search was conducted in the MEDLINE, EMBASE and Web of Science databases to select studies conducted since 2010 with therapeutic monitoring data of beta-lactams in septic children. Last searches were performed on 02 September 2021. Two independent authors selected the studies and extracted the data. A narrative and qualitative approach was used to summarize the findings. Out of the 118 identified articles, 21 met the eligibility criteria. Population pharmacokinetic modeling was performed in 12 studies, while 9 studies reported data from bedside monitoring of beta-lactams. Most studies were conducted in the United States of America (n=9) and France (n=5) and reported PK/PD data of amoxicillin, ampicillin, azlocillin, aztreonam, cefazolin, cefepime, cefotaxime, ceftaroline, ceftazidime, doripenem, meropenem and piperacillin/tazobactam. Therapeutic targets ranged from to 40% fT> MIC to 100% ƒT> 6× MIC. Prolonging the infusion time and frequency were most described strategies to increase target attainment. Monitoring beta-lactam serum concentrations in clinical practice may potentially maximize antimicrobial effectiveness. Further studies are required to define the therapeutic target associated with the best clinical outcomes.